The Athenian Nation - Cohen, Edward E. (Book collections on Project MUSE., 2000)
Challenging the modern assumption that ancient Athens is best understood as a polis, Edward Cohen boldly recasts our understanding of Athenian political and social life. Cohen demonstrates that ancient sources referred to Athens not only as a polis, but also as a "nation" (ethnos), and that Athens did encompass the characteristics now used to identify a "nation."